Anterior chamber enhancement – a window into the orbital glymphatic system and beyond?. (20th December 2022) - Deike‐Hoffmann, Katerina; von Lampe, Paula; Eerikaeinen, Maija; Ting, Saskia; Schlüter, Sabrina; Schlemmer, Heinz‐Peter; Bechrakis, Nikolaos; Forsting, Michael; Radbruch, Alexander
Abstract: Background: Recently, an orbital glymphatic system (GS) was described, that serves retinal homeostasis and clearance. In accordance to the brain GS, the orbital GS is supposed to be altered in a variety of disease, first and foremost Alzheimer's Disease (AD). Disturbances of the orbtial GS where suggested to serve as early (imaging) biomarker. Therefore it is highly desirable to visualize orbital GS function in vivo. This study investigated intravenously injected Gadolinium‐based contrast agent (GBCA) to visualize the orbital GS. We used a retrospective patient cohort of children suffering from retinoblastoma (RB) who are supposed to show altered orbital GS function to test the validity of this method. Method: This IRB approved retrospective single‐center study encompassed 539 orbital MRIs performed with an orbital coil and with the children in a state of general anesthesia. Differences of signal intensity ratios of the AC to the lens (∆SIRs) were determined between native and GBCA‐enhanced T1‐weighted images. Subsequently, ∆SIRs were correlated with histopathologic tumor features such as infiltration of the ON, choroid, ciliary body, sclera and AC. Result: ∆SIR of the RB eye was an independent, significant predictor for ON infiltration in multivariate analysis with adjustment for tumor size (p < 0.05) and increased with infiltration level (compare fig. 1A+B). ∆SIR was not predictive for any other assessed histopathologic tumor feature. Conclusion: GBCA enhancement of the AC predicts ON infiltration by RB. This might be caused by impairment of the orbital GS, which is supposed to clear toxic metabolites from the retina to the postlaminar ON (compare fig. 2). In RB with ON infiltration, this efflux path might be inhibited, which is supposed to result in disturbed retinal homeostasis, release of vascular endothelial growth factor and iris neovascularization with increased penetration of GBCA into the AC (compare fig. 3). We conclude, that GBCA‐enhanced MRI might enable visualization of (orbital) GS function in vivo and suggest assessment of this imaging approach in patients with neurodegenerative diseases.